2010
DOI: 10.1021/ac100984h
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Gemcitabine Incorporation into Human DNA by LC/MS/MS as a Surrogate Measure for Target Engagement

Abstract: In this study, we report a method for direct determination of gemcitabine incorporation into human DNA. Gemcitabine (dFdC), a structural analog of the nucleoside deoxycytidine (dC), derives its primary antitumor activity through interruption of DNA synthesis. Unlike other surrogate measures, DNA incorporation provides a mechanistic end point useful for dose optimization. DNA samples (ca. 25 microg) were hydrolyzed using a two-step enzymatic procedure to release dFdC which was subsequently quantified by LC-ESI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
(21 reference statements)
1
19
1
Order By: Relevance
“…This phenomenon potentially explains the results for two of our responsive patients who had low microdose-induced carboplatin-DNA adducts. To address this issue, we used gemcitabine microdosing in PDX bearing mice, which has only previously been reported in cell culture (47). Our study indeed showed that the levels of gemcitabine incorporated into DNA correlated with the response of PDXs to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon potentially explains the results for two of our responsive patients who had low microdose-induced carboplatin-DNA adducts. To address this issue, we used gemcitabine microdosing in PDX bearing mice, which has only previously been reported in cell culture (47). Our study indeed showed that the levels of gemcitabine incorporated into DNA correlated with the response of PDXs to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of the gemcitabine (dFdC), which is a nucleoside analog of deoxycytidine, was measured using a highly sensitive liquid chromatography/mass spectrometric assay that measured the amount of dFdC incorporated into genomic DNA [11]. Peripheral whole blood samples were collected prior to the administration of gemcitabine on study days 1, 8, and 15 and on days 5 and 19.…”
Section: Methodsmentioning
confidence: 99%
“…After the DNA had been isolated and completely hydrolyzed, the fluorinated nucleotide (dFdC) was detected using LC/MS-MS (20).…”
Section: Pharmacokineticsmentioning
confidence: 99%